Characteristics and findings of digital subtraction angiography and magnetic resonance imaging in neurological patients: a cross-sectional study - Sumantri, Fritz; Adriani, Dini; Novitasari, Ratih W.; Lomboan, Veinels C.; Kurnia, Leny; Kastilong, Merlin P. (International Journal of Research in Medical Sciences, 2024)
Background: Stroke is a major health concern worldwide with significant rates of mortality and morbidity. Asian population suffers from increasing incidence of stroke. Various imaging modalities have been developed for the diagnosis of stroke and neurological diseases. This study aims to compare the use of digital subtraction angiography (DSA) and magnetic resonance imaging (MRI) in neurological patients, underscoring particularly in ischemic stroke patients. Methods: This cross-sectional descriptive study was performed from February to November 2023. Data was taken from medical records. All patients visiting the outpatient care unit of a hospital in Jakarta who underwent DSA and MRI were included in the study. The data taken included the patient’s name, medical record number, age, gender, MRI results, DSA results, and diagnosis. Diagnosis was established through history taking and physical examination. Results: Of 500 subjects included in the study, most subjects were male (50.6%) aged 20 – 60 years old (75.6%) abnormal MRI and DSA results (84.6% and 90.6%, respectively). Ischemic stroke was the leading diagnosis (50.8%). MRI and DSA results showed 79.6% agreement of all cases. Conclusions: Although MRI showed normal results, DSA could show abnormal results. This points out DSA superiority in detecting vascular abnormality compared to MRI.